2011
DOI: 10.1016/j.biochi.2011.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Heparin affects the interaction of kininogen on endothelial cells

Abstract: In the plasma kallikrein-kinin system, it has been shown that when plasma prekallikrein (PK) and high molecular weight kininogen (HK) assemble on endothelial cells, plasma kallikrein (huPK) becomes available to cleave HK, releasing bradykinin, a potent mediator of the inflammatory response. Because the formation of soluble glycosaminoglycans occurs concomitantly during the inflammatory processes, the effect of these polysaccharides on the interaction of HK on the cell surface or extracellular matrix (ECM) of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Indeed it is well known that GAGs interact with H-kininogen at the endothelial cell surface [9], [11], [27], as well as GAGs also interact with plasma kallikrein modifying its kinetics behavior [36], [37]. Prekallikrein interaction with cells may generate plasma kallikrein by proteolytic cleavage and its activity can be analyzed by H-kininogen structure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed it is well known that GAGs interact with H-kininogen at the endothelial cell surface [9], [11], [27], as well as GAGs also interact with plasma kallikrein modifying its kinetics behavior [36], [37]. Prekallikrein interaction with cells may generate plasma kallikrein by proteolytic cleavage and its activity can be analyzed by H-kininogen structure.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma kallikrein-kinin proteins have also been found on the surface and in the extracellular matrix of endothelial cells from line ECV304 [23], vascular smooth muscle cells [24], immortalized human EA.hy926 endothelial cells [25], lung epithelial cells [26] and endothelial cells from a line derived from rabbit aorta RAECs [27]. Little is known regarding the mechanisms of plasma prekallikrein interactions with cells.…”
Section: Introductionmentioning
confidence: 99%
“…On the cell surface, H-kininogen binds to heparan sulfate (HS) or chondroitin sulfate (CS) proteoglycans (PGs) [ 13 ], [ 14 ], and HSPG appear to play a critical role in recruiting kinin precursors from the plasma and in the assembly of components triggering the release of active kinins from their precursors in proximity to their target cells [ 15 ]. Indeed, glycosaminoglycans (GAGs) that accumulate in the inflammatory fluids could act as pro- or anti-inflammatory mediators depending on different factors within the cell environment [ 16 ]. The H-kininogen interaction with HS on the cell surface results in its endocytosis into acidic vessels [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…37 Further evidence supporting a potentially specific role of HS in localizing HK to the cellular surface comes from experiments that show reduced surface HK surface binding in the presence of soluble HS in rabbit aorta endothelial cells. 38 A potential mechanism for how HS could influence bradykinin cleavage on the cellular surface is through defects in cellular uptake; it has been shown that HS proteoglycans mediate endocytosis of HK, 39,40 which could have potential influence on bradykinin generation and/or targeting. This leads us to the following hypothesis regarding the effect of the HS3ST6 mutation on angioedema formation in the patients with HAE who belonged to the family described in this study.…”
Section: Discussionmentioning
confidence: 99%